Stories that Make History The Experience and Memories of the Japanese Military ›Comfort Girls-Women‹ - Research Team of the War, The; Human Rights Center, Women's (Genocide and Mass Violence in the Age of Extremes, 2020)
The experiences of Korean comfort girls-women are a paradigmatic example of how military sexual violence can obliterate the dignity of women and shame them into nonexistence. This book examines how the turning of their innocence into inadequacy, compounded their long, miserable suffering for half a century.